2018
DOI: 10.3390/cancers10120496
|View full text |Cite
|
Sign up to set email alerts
|

PHD3 Acts as Tumor Suppressor in Mouse Osteosarcoma and Influences Tumor Vascularization via PDGF-C Signaling

Abstract: Cancer cell proliferation and insufficient blood supply can lead to the development of hypoxic areas in the tumor tissue. The adaptation to the hypoxic environment is mediated by a transcriptional complex called hypoxia-inducible factor (HIF). HIF protein levels are tightly controlled by oxygen-dependent prolyl hydroxylase domain proteins (PHDs). However, the precise roles of these enzymes in tumor progression and their downstream signaling pathways are not fully characterized. Here, we study PHD3 function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Possible targets for anti‐angiogenesis therapies include transcription factors or signal pathways that directly or indirectly affect VEGF, PDGF, fibroblast growth factor (FGF), hepatocyte growth factor, integrin, cyclooxygenase (COX‐2), metalloproteinases (MMP‐2, MMP‐9) and HIF‐1. 19 , 20 , 21 VEGF and its receptors (VEGFRs) are key mediators of angiogenesis in cancer.…”
Section: Tumour Angiogenesis In Osmentioning
confidence: 99%
“…Possible targets for anti‐angiogenesis therapies include transcription factors or signal pathways that directly or indirectly affect VEGF, PDGF, fibroblast growth factor (FGF), hepatocyte growth factor, integrin, cyclooxygenase (COX‐2), metalloproteinases (MMP‐2, MMP‐9) and HIF‐1. 19 , 20 , 21 VEGF and its receptors (VEGFRs) are key mediators of angiogenesis in cancer.…”
Section: Tumour Angiogenesis In Osmentioning
confidence: 99%
“…The details of all signaling pathway networks identified were also shown in Figures 6A-C (A: numbers of ligand receptors among all cell types; B: weights of ligand receptors among all cell types; C: chordal graph of ligand-receptor interactions among all cell types). Among the total of 57 signaling pathways, the following signaling pathways were related to osteosarcoma: COLLAGEN ( Baumann and Hennet, 2016 ; Elenjord et al, 2009 ; Levinson et al, 2002 ; Yamaguchi et al, 2005 ), CD99 ( Manara et al, 2006 ; Sciandra et al, 2014 ; Zucchini et al, 2014 ), PTN ( He et al, 2019 ; Qin et al, 2022 ; Sun et al, 2020 ), MIF( Liu et al, 2014 ), SPP1( Dalla-Torre et al, 2006 ; Li et al, 2017 ), FN1( Saba et al, 2019 ; Zhou et al, 2019 ), LAMININ( Heino and Massague, 1989 ), FGF ( Kurogi et al, 1996 ; Laulederkind et al, 2000 ; Li et al, 2019 ; Xu et al, 2010 ), VEGF ( Ji et al, 2020 ; Lei et al, 2018 ; Oda et al, 2006 ; Tsai et al, 2017 ; Zhang et al, 2019 ), GALECTIN( Gomez-Brouchet et al, 2010 ; Miao et al, 2014 ; Park et al, 2015 ; Zhou et al, 2014 ), PERIOSTIN( Ma et al, 2020 ; Xu et al, 2022 ), VISFATIN( Cheng et al, 2015 ; Wang et al, 2019 , 2016 ), ITGB2 ( Dai et al, 2018 ), NOTCH( Jin et al, 2017 ; Mu et al, 2013 ; Ongaro et al, 2016 ; Tanaka et al, 2009 ; Zhang et al, 2010 ), IGF ( Armakolas et al, 2016 ; Giatagana et al, 2022 ; Gvozdenovic et al, 2017 ; Molina et al, 2019 ; Tan et al, 2015 ), VWF( Wang et al, 2020 ), and PDGF ( Chen et al, 2009 ; Egners et al, 2018 ; Heldin et al, 1986 ). The ligand-receptor interact...…”
Section: Resultsmentioning
confidence: 99%
“…In gastric cancer, cell migration and invasion were significantly higher in PHD3-silenced tumor cells than controls, and both HIF1 and VEGF showed greater expression [141]. In mouse LM8 osteosarcoma, we showed that PHD3 is a tumor suppressor as silencing of this oxygen sensor led to enhanced tumor growth and dramatically changed vessel morphology that was directly related to significantly activated platelet-derived growth factor (PDGF)-C signaling in the vasculature of PHD3 knockdown tumors [142]. Thus, the impact of the PHDs in tumor progression is diverse and cell-dependent, i.e., tumor cell vs. TME.…”
Section: The Phd-hif Axis As a Central Regulator Of Tumor Developmentmentioning
confidence: 87%